Delivery of a multi-focus public health intervention in the paediatric emergency department: a feasibility and acceptability pilot study - Rachel Isba; Rhiannon Edge (BMJ Open)
Objective The objective was to see if it was feasible and acceptable to deliver a brief public health intervention as part of an attendance at the paediatric emergency department (PED).Design A feasibility and acceptability pilot design was used as there is no previous work done in this clinical area, population or using this approach in children and young people (CYP). Quantitative and qualitative data were collected. Follow-up was at 1 week and 1, 3 and 6 months.Setting This pilot took place in a single PED in Greater Manchester, England.Participants Participants were CYP (under 16 years old) and their parents/carers, attending the PED during a 2-week recruitment period in September 2019.Interventions The intervention was a brief conversation with a Consultant in Paediatric Public Health Medicine, using Screening, Brief Intervention and Referral to Treatment. The intervention focused on vaccination, dental health, household smoking and frequent attendance.Primary and secondary outcome measures The primary outcome measure was information to support the effective development of a larger-scale study. Secondary outcomes were measures of health, again intended to provide additional information prior to a larger study.Results Thirty CYP were recruited from 29 households. Sixty per cent of CYP triggered at least one screening question, most commonly household smoking and dental health. It was not possible to accurately assess frequent attendance and 97% of parents/carers stated that they thought their child or young person was fully vaccinated for their age, which is likely to be an over-estimate.Conclusions It is feasible to deliver a brief public health intervention in the PED and such an approach is acceptable to a variety of stakeholders including CYP, parents/carers and nursing staff. The pilot revealed issues around data quality and access. Future work will focus on vaccination and dental health.